A new conceptual model for seed germination and seedling tillering of winter wheat in the field - Jinping Chen; Peter A. Whalley; Zhongyang Li; Xiaoxian Zhang; Malcolm J. Hawkesford; W. Richard Whalley (Royal Society Open Science)
Seed germination is a crucial stage in plant development, intricately regulated by various environmental stimuli. Understanding these interactions is essential for optimizing planting and seedling management but remains challenging due to the trade-off effects of environmental factors on the germination process. We proposed a new conceptual model by viewing seed germination as a dynamic process in a physiological dimension, with the influence of environmental factors and seed heterogeneity characterized by a germination speed and a dispersion coefficient. To validate the model, we conducted field experiments by drilling wheat seeds at different dates to establish a temperature gradient and in different plots to create a soil water content gradient. Comparisons with our experimental data and literature results show the model accurately reproduces all germination patterns and the subsequent seedling tillering, with R2 > 0.95. Our results reveal that within suboptimal temperature range, the seed germination increases asymptotically with temperature, and that as soil water content increases, the germination speed increases initially before decreasing, illustrating the trade-off effect of soil water on bioavailability of water and oxygen. Introducing a physiological dimension enables seed germination and the subsequent tillering process to be modelled as a continuous physiological process, providing deeper insight into plant growth dynamics.